The effect of selected pesticides on the growth and nitrogen fixation in cyanobacteria - Güner (Sıvacı), Sima. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1992., 1992)
Algae, in general, are the primitive form of higher plants and they are found in water bodies and in moist locations such as tree trunks, walls, rocks and damp soil. Many species are found in all parts of the world, from the tropics to the polar regions. Water , light, temperature and the chemical composition of the medium are the factors that may stimulate or prevent the growth. The elements essential for the growth of algae are the same as those necessary for the growth of higher plants. Algae are used for the removal of pesticides from the aquatic environment, therefore their functions and responses to external effects resulting from the use of chemicals are of concern. The choice of algal species for bioassays is partly based on algae being the primary producers in aquatic ecosystems. Since pesticides are pollutants, it is better to analyze them on these living organisms, which can give an information about other higher plants. Contamination of aquatic and soil environments by pesticides results from agricultural origin. Pesticides enter the environment by direct or indirect routes. These agents can be sprayed on crops or dispersed in the field as a granular substance. Such pesticides are introduced directly into the aquatic environment. The cleaning of industrial mixing equipment, disposal of waste and accidents increase the amount of pesticides found in soil and water. Rain and other precipitation can carry pollutants to the fresh water systems, so causing harmful effects for the algae. The application of pesticides for plant protection and their persistent residues has direct effect on the fresh water algae and consequently the soil fertility. These pesticides applied directly or indirectly to soil may upset the ecological balance of the soil. This situation clearly explains the importance of studying the effects of pesticides on the different physiological and biological processes. Algal studies are recently well documented. Recent studies involve the use of some pesticides on algal cultures in order to examine their effects on growth and nitrogen fixation. Effects of chemical agents could quickly be investigated with blue-green algae before testing pesticides on higher plants. The aim of this study was to examine the toxicity effects of a herbicide 2,4- dichelorophenoxyacetic acid (2,4-D) and an insecticide methyl parathion on two algal species, one being a heterocystous filamentous cyanobacteria Anabaena cylindrica and the other, unicellular cyanobacteria Gloeocapsa. Toxicity determinations were based on the growth measurements of these species. Moreover, a specific property of blue-green algae, nitrogen fixing ability was determined by using acetylene reduction technique. During the experiments light intensity, temperature and pH were under the control.
Keywords: Algae.; Cyanobacteria -- Toxicology.; Pesticides -- Environmental aspects.